Postoperative Sepsis: A Clinical Audit of Obstetrics and Gynecological Cases - Dr Sushma Rachel S, Dr Joylene Diana D’Almeida (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Postoperative sepsis is a major cause of illness and death after major surgeries, especiallygynecological procedures, even with improvements in cleanliness and antibiotic use. This auditaimed to assess how often postoperative sepsis occurs, the types of microbes involved, and the risk factors linked to it in a tertiary care hospital.